From Separate Legal Entity to Economic Unity: The Criminal Liability of Parent Company - Ali, Mahrus (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2019)
Corporate criminal liability has become an issue following the increase in corporate crimes. This study discusses the possibility of parent company to deny liability for crimes committed by its subsidiary companies. This normative legal research employed qualitative analysis. The results showed that the parent company denied criminal liability by hiding behind the separate legal entities and limited liability doctrine. Through both doctrines, the parent company treats itself as a separate legal entity apart from the subsidiary company so that the former holds no liability for any crime committed by latter. Through piercing the corporate veil doctrine, the parent company intentionally uses the subsidiary company as a tool to maximize profits and applies total control. Therefore, based on the vicarious liability principle, the subsidiary company functioned as the parent company’s agent. It works for or on behalf of the parent company in which every profit made is owned by the parent company.